Effect of Preschool Classroom Quality on Social and Language Development - (:unkn) unknown (My University, 2012)
The purpose of this study was to examine the effect of child care classroom quality on language and social outcomes for economically disadvantaged preschool youth who have been enrolled in a high-quality preschool program for one year. The study investigated preschool children's receptive language ability and social development in relation to environmental quality and teacher-child interaction quality, while controlling for child and teacher gender, teacher level of education, children's dominant language, and children's initial performance on measures of receptive language and social development, as assessed by the PPVT-IV and DECA-C, respectively. The sample was drawn from a specific model of high quality child care education centers located in urban areas throughout the United States. Survey, child assessment, and observation data used in the present study are part of a larger study known as the Educare Learning Network Implementation Study. The Implementation Study is a partnership between the Ounce of Prevention Fund and Frank Porter Graham Child Development Institute at the University of North Carolina. Principal investigators for the Educare Learning Network Implementation Study are Noreen Yazejian and Donna Bryant. For the present study, child care classroom environmental quality was examined as a broad construct using the Early Childhood Environment Rating Scale - Revised (ECERS-R; Harms, Clifford, & Cryer, 1998), and the quality of teacher-child interactions was explored in-depth using the Classroom Assessment Scoring System (CLASS; Pianta, La Paro, & Hamre, 2008). Hierarchical linear modeling was used to analyze the impact of quality on children's receptive vocabulary and social competency. Overall classroom quality, as assessed through the ECERS-R, was not related significantly to any of the measured child outcomes. With regard to teacher-child interaction quality, as assessed by the CLASS, results indicated that the quality of emotional support and classroom organization were significantly predictive of children's behavioral concerns. In particular, higher quality emotional support and classroom organization predicted fewer behavioral concerns at school. Together the results suggest that classroom quality factors may impact on students' development of social competencies, however, the results of the present study did not indicate a link between classroom factors and young children's development of early literacy. Possible explanations for the study findings, along with study limitations, are discussed.
Keywords: Classroom Quality; Early Childhood Education; Language Development; Preschool Quality; Social Competence; Teacher-Child Interaction